Australian Aboriginal children with otitis media have reduced antibody titers to specific nontypeable Haemophilus influenzae vaccine antigens - Thornton, R.; Kirkham, L.; Corscadden, K.; Wiertsema, S.; Fuery, A.; Jones, B.; Coates, H.; Vijayasekaran, S.; Zhang, Guicheng; Keil, A.; Richmond, P. (American Society of Microbiology, 2017)
Indigenous populations experience high rates of otitis media (OM), with increased chronicity and severity, compared to those experienced by their nonindigenous counterparts. Data on immune responses to otopathogenic bacteria in these high-risk populations are lacking. Nontypeable Haemophilus influenzae (NTHi) is the predominant otopathogen in Australia. No vaccines are currently licensed to target NTHi; however, protein D (PD) from NTHi is included as a carrier protein in the 10-valent pneumococcal polysaccharide conjugate vaccine (PHiD10-CV), and other promising protein vaccine candidates exist, including outer membrane protein 4 (P4) and protein 6 (P6). We measured the levels of serum and salivary IgA and IgG against PD, P4, and P6 in Aboriginal and non-Aboriginal children with chronic OM who were undergoing surgery and compared the levels with those in healthy non-Aboriginal children (controls). We found that Aboriginal cases had lower serum IgG titers to all NTHi proteins assessed, particularly PD. In contrast, serum IgA and salivary IgA and IgG titers to each of these 3 proteins were equivalent to or higher than those in both non-Aboriginal cases and healthy controls. While serum antibody levels increased with age in healthy controls, no changes in titers were observed with age in non-Aboriginal cases, and a trend toward decreasing titers with age was observed in Aboriginal cases. This suggests that decreased serum IgG responses to NTHi outer membrane proteins may contribute to the development of chronic and severe OM in Australian Aboriginal children and other indigenous populations. These data are important for understanding the potential benefits of PHiD10-CV implementation and the development of NTHi protein-based vaccines for indigenous populations.